Epispadias, a correctable cause of structural infertility in a middle-aged man: a case report - Mustapha Kura; Khalifa Ibrahim Abdulsalam; Afolayan Ayodeji; Abayomi Arogundade; David Ezekiel (African Journal of Urology, 2024)
Abstract Background Epispadias is a rare form of genito-urinary congenital anomaly and presentation in the middle-ages is even rarer. The reproductive outcome of treatment which was almost immediate, highlights the life changing effect of appropriate treatment for this condition in a middle-aged patient. We hereby report this rare case of a middle-aged man presenting with complete male epispadias with background infertility and the outcome of effective treatment. (Reviewer #1. Comment 1). Case presentation Our patient is a 54-year-old security guard who presented to our facility in February 2022 (Reviewer #1. Comment 3) with passage of urine from an abnormal opening since birth. Examination revealed a middle-aged man having ammoniacal smell. He had a spade like glans penis, ventral hooding, urethral meatus at the root of the penis dorsally with no chordee. He was diagnosed to have complete male epispadias (CME) for which he eventually had a modified Cantwell–Ransley procedure under general anaesthesia. About 3 months after the procedure, patient was able to impregnate his wife, a feat he will be achieving for the first time in his life. Conclusions The right treatment irrespective of age at presentation could significantly improve the quality of life of patients as evidenced by our patient whom after surgery was able to impregnate his wife for the first time at 54 years of age.